2019
DOI: 10.1108/pmm-06-2019-0024
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly research in Library and Information Science: an analysis based on ISI Web of Science

Abstract: Purpose The purpose of this paper is to present a quantitative analysis of the Library and Information Science (LIS) scholarly literature published worldwide. Design/methodology/approach The ISI Web of Science database was used as a source for extracting the data of published documents during the period 2003–2017. The analysis of the published literature was based on the following indicators: research productivity of each county, annual publications, annual citations, highly cited articles, highly cited LIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 37 publications
3
20
0
Order By: Relevance
“…They also revealed that the world’s leading institutional producers are situated in the United States. This part was corroborated by Ahmad et al (2019) and Sin (2011).…”
Section: Literature Reviewsupporting
confidence: 57%
“…They also revealed that the world’s leading institutional producers are situated in the United States. This part was corroborated by Ahmad et al (2019) and Sin (2011).…”
Section: Literature Reviewsupporting
confidence: 57%
“…The results showed the highest cited articles (with JASIST publishing half of the top 10 most‐cited articles during the period), number of publications by country (e.g., led by the United States with 39% of all publications), journals whose articles received the most citations (i.e., Journal of the Medical Library Association received the most), and most prolific authors (most‐published authors in the Web of Science index of journals, with M. Thelwall having the most). Ahmad et al (2020) dove into specifics of these findings, noting, for instance, that the top authors did not originate from any specific field/specialization within LIS. They also identified top institutions for these publications, with authors from Indiana University and the University of Illinois at the top.…”
Section: Literature Reviewmentioning
confidence: 97%
“…Another study utilizing Web of Science data to analyze LIS research literature published from 2003 to 2017 was conducted by Ahmad, Sheikh, and Rafi (2020). The results showed the highest cited articles (with JASIST publishing half of the top 10 most-cited articles during the period), number of publications by country (e.g., led by the United States with 39% of all publications), journals whose articles received the most citations (i.e., Journal of the Medical Library Association received the most), and most prolific authors (most-published authors in the Web of Science index of journals, with M. Thelwall having the most).…”
mentioning
confidence: 99%
“…This new conceptualization of information literacy is more appropriate and useful in studying the information literacy of individuals from developing countries (Lloyd & Wilkinson, 2017). Upon examining Scopus and Web of Science databases, several bibliometric studies find that the LIS publications authored by researchers in developed countries disproportionately outnumber the ones authored by researchers in developing countries (Ahmad et al, 2019; Islam & Roy, 2021; Siddique et al, 2020).…”
Section: Introductionmentioning
confidence: 99%